APPLICATION OF VECTORS IN SOLVING PLANIMETRIC PROBLEMS - Bozorov Zakir Yuldosh ogli; Sattorov Sardar Abdimuradovich; Muhammadiev Zohidjon Hasan ogli (Western European Studies, 2025)
This article analyzes the advantages and practical significance of using the vector method in solving planimetric problems. The vector method allows you to express the relationships between geometric figures in algebraic form, which simplifies and generalizes the process of solving problems. The article considers solutions to planimetric problems involving triangles, parallelograms, circles, and other geometric figures using vector operations - addition, subtraction, scalar and vector products. The vector method provides greater logical consistency compared to traditional geometric approaches, reduces calculation errors, and serves to develop students' spatial and analytical thinking. The results of the study show that the use of the vector method in the planimetry course is an effective tool for students to develop a deeper understanding of mathematical concepts and independent thinking skills.
Keywords: Vector; geometric problem; collinear vectors